an J Health Educ Health Promot 2018
DOI: 10.30699/acadpub.ijhehp.5.4.296
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education Based on Self-efficacy Theory on Health Literacy, Self-efficacy and Self-care Behaviors in Patients With Type 2 Diabetes

Abstract: Background and Objective: Type 2 diabetes is one of the most important public health challenges. Self-efficacy and health literacy play a key role in self-care for diabetic patients. The aim of this study was to determine the effect of training based on self-efficacy theory on health literacy, self-care behaviors and self-efficacy in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 0 publications
2
31
1
Order By: Relevance
“…After the educational intervention, the number of patients whose health literacy was improved significantly increased and it is reasonable to expect a significant decrease in the percentage of T2D patients with low levels of health literacy. Similar results in consistent with ours have been reported on the enhancing of health literacy as a function of theory-based education impact [ 40 , 41 ]. Some studies have emphasized the necessity of designing and implementing educational interventions equal to the level of health literacy of patients, and shown that the determinants of health behaviors in patients with various levels of health literacy significantly differ; to this end, the same interventional strategies shouldn’t be designated.…”
Section: Discussionsupporting
confidence: 92%
“…After the educational intervention, the number of patients whose health literacy was improved significantly increased and it is reasonable to expect a significant decrease in the percentage of T2D patients with low levels of health literacy. Similar results in consistent with ours have been reported on the enhancing of health literacy as a function of theory-based education impact [ 40 , 41 ]. Some studies have emphasized the necessity of designing and implementing educational interventions equal to the level of health literacy of patients, and shown that the determinants of health behaviors in patients with various levels of health literacy significantly differ; to this end, the same interventional strategies shouldn’t be designated.…”
Section: Discussionsupporting
confidence: 92%
“…Of 52 included studies, 25 (48%) studies included populations with health conditions [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and 24 (46.3%) studies included patient participants with chronic disease [ 12 , 27 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], and other disease (3/52; 5.7%) [ 55 , 56 , 59 ] ( Table 1 ). We included 45 cross-sectional studies […”
Section: Resultsmentioning
confidence: 99%
“…A large body of studies has indicated the effect of education based on health training and health promotion models on the changes in health literacy scores during the training period, including Hejazi et al, (26) who observed significant changes in literacy scores in the experimental group after studying based on self-efficacy model. Tol et al evaluated the effect of training program in the form of small groups on health literacy and observed a significant difference in health literacy scores after training intervention (27).…”
Section: Ms Associationmentioning
confidence: 99%